Review on Ferroelectrics in Developing Novel Solar Cells - Xiao, Jingzhong; A. Paixiao, Jose.; M. R. Costa, Maria; Sun, Dunlu (Recent Patents on Materials Science, 2012)
The study in ferroelectric photovoltaic (PV) effect has become an important topic in fields of condensed matter physics and materials sciences in recent years. For the rapidly growing needs in solar energy, the interest in developing ferroelectric PV devices with specific properties has drastically increased. This paper firstly focuses on the fundamental aspects of PV effect in ferroelectric materials, and presents a review on the latest developments in ferroelectric PV cells. For the application of ferroelectrics on solar cells, relevant patents are also presented and discussed, to describe the main characteristics of ferroelectric PV cells and achieve the understanding on their future development.
Keywords: solar cells